Meningioma as a Rare Presentation - Mais Almumen; Liqaa Mohammed Muslim; Ammar Saeed Rasheed (مجلة الكوفة الطبية)
Background: The most common extra axial primary central nervous system (CNS) tumor is meningioma, accounting for 36% of all CNS tumors. On neuroradiologic and gross assessment, the typical meningioma is lobulated. Cystic variants, although uncommon, are well recognized, and possibly be confused with metastatic or glial tumors. Case presentation: A 40-year-old female patient complaining of headache, Magnetic resonance imaging (MRI) revealed frontoparietal brain cystic lesion with intracystic nodule, given the differential diagnosis of low-grade gliomas, hemangioblastoma, pleomorphic xanthoastrocytoma, pilocytic astrocytoma and rarely meningioma. The histopathological slides showed the diagnosis of meningothelial meningioma (WHO/Mayo Clinic_ Grade I). Immunohistochemistry (IHC) was performed for epithelial membrane antigen (EMA) showing positive membranous stain but IHC staining for glial fibrillary acetic protein (GFAP) was negative for the cytoplasm.  Conclusions: Patient with cystic meningioma was reported. There is no absolute test for preoperatively distinguishing it from the most prevalent other gliomas. So avoiding any extra cost and time loss, angiographic assessment and cooperation with a histopathologist are of clinical importance for the identification of these possibly curable neoplasms.